“Golden parachute” is to Save the Top-Manager? - Nikolai A. Potapov (Московский журнал международного права, 2014)
“Golden parachute” is a prerogative of the top management of joint stock companies. Such tools are used in large companies; the “Golden parachute” has two functions: protection of the management and protection of the possible seizure of the company (absorption).The article carries out a comparative analysis of “Golden parachutes” abroad and in Russia, considers the question about the payment of these instruments from a practical point of view. The author attempts to consider the “Golden parachutes” as a negative phenomenon, which is used in practice as an instrument of abuse of the right and the way to deal with the redemption of shares under the mandatory offer.